Testing the Theory of Resilience and Relational Load (TRRL) in Families with Type I Diabetes. Issue 10 (24th August 2019) - Afifi, Tamara; Granger, Douglas; Ersig, Anne; Tsalikian, Eva; Shahnazi, Ariana; Davis, Sharde; Harrison, Kathryn; Acevedo Callejas, Michelle; Scranton, Audrey
ABSTRACT: The theory of resilience and relational load was tested with 60 couples and their adolescent children (ages 11–18) with type I diabetes (T1D). The couples participated in a stress-inducing conversation task in their home, followed by a random assignment to a two-week intervention designed to increase their relationship maintenance. Before the intervention, stronger communal orientation predicted greater maintenance for husbands and wives, but maintenance only reduced T1D stress for wives. The wives' and adolescents' T1D stress were also correlated, but the husbands' T1D stress was not significantly associated with either of them. Better maintenance was associated with less conflict during couples' conversations. Maintenance was also directly associated with less perceived and physiological stress (cortisol) from the conversation. Finally, wives in the intervention reported the most thriving, communal orientation and the least loneliness. The intervention also reduced adolescents' general life stress, but it did not influence their T1D stress or thriving.